计算1.(3a+2)^2 2.(a+1)(a-1)(a^2-1) 解方程8x^3+3(x-1)(x+1)-(3X+2)(x-3)=(1+2X+4x^2)(2X-1)

问题描述:

计算1.(3a+2)^2 2.(a+1)(a-1)(a^2-1) 解方程8x^3+3(x-1)(x+1)-(3X+2)(x-3)=(1+2X+4x^2)(2X-1)
计算1.(3a+2)^2
2.(a+1)(a-1)(a^2-1)
解方程8x^3+3(x-1)(x+1)-(3X+2)(x-3)=(1+2X+4x^2)(2X-1)

1.(3a+2)^2
=9a^2+12a+4
2.(a+1)(a-1)(a^2-1)
=(a^2-1)(a^2-1)
=(a^2-1)^2
=a^4-2a^2+1
8x^3+3(x-1)(x+1)-(3X+2)(x-3)=(1+2X+4x^2)(2X-1)
8x^3+3(x-1)(x+1)-(3X+2)(x-3)=8x^3-1
3(x-1)(x+1)-(3X+2)(x-3)=-1
3(x^2-1)-(3x^2--x-6)=-1
3x^2-3-3x^2+x+6=-1
x+3=-1
x=-4你确定最后一题正确??8x^3+3(x-1)(x+1)-(3X+2)(x-3)=(1+2X+4x^2)(2X-1)8x^3+3(x-1)(x+1)-(3X+2)(x-3)=8x^3-13(x-1)(x+1)-(3X+2)(x-3)=-13(x^2-1)-(3x^2-7x-6)=-13x^2-3-3x^2+7x+6=-17x+3=-17x=-4x=-4/7.. 嗯 .满意了.!!